SINTESIS METIL ESTER DARI MINYAK BIJI KARET (Hevea brasiliensis ) SEBAGAI BIODIESEL DENGAN KATALIS ABU BUAH BINTARO(Cebera manghas L.) - Bagus Muliawan; Subur P Pasaribu; Aman Sentosa Panggabean (PROSIDING SEMINAR KIMIA, 2013)
The synthesis of methyl esters from rubber seed oil (Hevea brasiliensis) as biodiesel, using fruit bintaro ash utilization as a source of base catalysts in the transesterification reaction has been conducted. The determination of the base content in the fruit ash bintaro have been researched with alkalinity titration and K ion content determinated with Atomic Absorption Spectrophotometer. Base catalyst were obtained ash bintaro fruit mixed in methanol and used for the transesterification of rubber seed oil. Produce of biodiesel used with ash bintaro fruit weight of variety was 4-8 % (w/w). The fatty acid composition of rubber seed oil from transesterification results determined by using GC-MS, whereas some physical properties of biodiesel determined to know the quality of biodiesel. The results of research shows the of potassium contents in the form of potassium carbonate in ash bintaro fruit are 31.75% (w/w) and conversion of biodiesel obtained from each catalyst are 65.2; 66.6; 73.6; 69.8; and 69.2% (w / w) respectively. Data analiysis GC-MS dominant of fatty acids in the biodiesel contents are metil linoleatewith amount was 42.57%.